ENVIRONMENTAL CSR AND LOYALTY: THE ROLE OF GREEN IMAGE, BRAND PRESTIGE, AND INDIVIDUAL GREEN VALUES (Contemporary Journal of Social Science Review, 2025)
The paper examining the effects of the Environmental Corporate Social Responsibility (ECSR) in Pakistan and its effects on customer loyalty in the textile industry, which is facing more and more pressure to implement sustainable practices. Since environmentally friendly issues are increasingly becoming an important aspect among consumers, it becomes very essential to learn more about the relationship that exists between corporate sustainability and customer behavior. The overall objective of this study is to assess how ECSR works directly and indirectly on the customer loyalty with special emphases paid to the mediating effects of the Corporate Green Image, Brand Prestige, and individual Green Values. Based on the empirical data, obtained out of the textile consumers in Pakistan, the study determines the effect of the ECSR initiatives on the consumer perception, attitudes and loyalty. It tries to look at how the Corporate Green Image, which is the perceived environmental commitment of companies, is a major mediator that boosts the level of customer trust and brand association. Furthermore, the study considers the aspect of Brand Prestige, which implies the increasing impact of the perceptions of brand status and quality on the effects of loyalty brought about by ECSR. There is also analysis of Individual Green Values as a way of discernment of the influence of individual environmental beliefs and values in responses to corporate sustainability actions. The results of the conducted research are likely to offer theoretical and practical information. In theory, it advances earlier literature on sustainable marketing and customer behavior in terms of incorporating the roles of various mediators to the relationship between the ECSR and loyalty. Naturally, it provides strategic insight into what textile firms can do to enhance customer loyalty using specific sustainability efforts. Policymakers, as well as stakeholders interested in favoring the growth of environmentally responsible practices in the Pakistani textile industry, can also find the implications of the study in furthering their efforts towards achieving goals of sustainable development to the emerging market.